International purchasing offices under China context - yu, xiaoxuan (2012)
Abstract: Purpose- International sourcing has been gaining its popularity these years, and China is becoming a hotspot due to its low labor cost and recent developments. IPO, at the same time, is claimed to be one of the most popular way for a company to manage their offshore sourcing activities. Researches concerning the international sourcing and IPO operations in China have been covered, but most of them are not from managerial aspects, or country specific. Thus, the objective of this dissertation is to investigate the international sourcing and IPO related aspects under China context, and aims to provide suggested managerial approaches for the successful IPO operations. Methodology- The analysis of this study relied on qualitative research method, and the main data collection method were to conduct two semi-structured interviews with two managers of IPO in China. The results were presented by collective cross-interview analysis rather than only describing each interview in depth; Also, some recent literature were also draw on to compare with the information from both interviews, and they all contributed to identify the main features of the IPO success in China. Results- Finding of this study indicated that the advantage of sourcing in China has been shifting from low cost to its developing capabilities. In addition, the main functions that undertaken by IPO in China is sourcing, quality control and supportive functions. The reason that companies use IPO to manage their offshore sourcing is because IPO can eliminate culture differences as well as sourcing risks, etc. Further, this study proposed several managerial suggestions in order to help the IPO operations to be more effective. For example, managers of IPO are suggested to show strong leadership by interpersonal skills in China, rather than showing their authority always, since it is the best way to build trust and gain respect from employees. Also, it is beneficial to align IPO with the overall company strategy so that it can be consistently developed. Practical implications- This study has advanced the understanding regarding to IPO operations in China, and focus more from the managerial perspective, and try to analysis from a contemporary view. Also, this study is under China context, which is a country with vast potentials. The culture characteristics were integrated with the analysis of IPO operations or management in this study. It is believed that this study has contributed both in managerial aspects and theoretical aspects. Thus, this study has given some guidance to managers of IPO in China about how to maximize the efficiency of their IPO operations.